PENGEMBANGAN INSTRUMEN UNTUK MENGUKUR KEMAMPUAN REPRESENTASI DAN KOMUNIKASI MATEMATIS SISWA DALAM ASPEK FONETIK MATERI GEOMETRI SMP - Safitri, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrakThis research aimed to develop valid and appropriate test instruments to measura phonetical aspects of students’ mathaematical representation and communication in material about area and circumference of a circle. This research utilised formative research and development. The subjects of this study are tehe eight (VIII) grade students of SMP 9 Pontianak, during 2016/2017 academic year. There were 37 participants. The research found thet: (1) needs analusis found thar the teacher require to have test instruments that are suitable eith KTSP (education unit curriculum) due to differences between the old and test instruments that are being developed; (2) the validity of the test instruments about phonetical aspect of mathematic representation and communication of the aforementioned topic was 70%, reliability was 93%, distinguishing power was 32%, difficulty level was 32%, which can be categorized good; (3) in a 1-4 scoring scale, the students’ mathematical representation result showed thar, on average, top category students are 4, medium category students are3 and the bottom categorized students are 1. Keywords: Test Instrument, Representation Ability, Communicative Ability, Phonetical Aspect